Group Exhibition-Personal-Political Exhibition, Thessaloniki Biennale - Antoniou, Klitsa (My University, 2026)
Personal-Political Exhibition, Thessaloniki Biennale, Greece Curated by Areti Leopoulou and Theodore Markoglou